373 Evaluation of the Use of Water-Soluble Contrast Enema (CE) and Flexible Sigmoidoscopy (FS) prior to the Reversal of a Loop Ileostomy. (19th August 2022) - Elzaafarany, A; Nordin, MN; Narayan, P; Day, A
Abstract: Aim: To evaluate the routine use of CE and FS to check integrity of anastomosis prior to reversal of a loop ileostomy. Method: This is a single centre retrospective observation study. All patients who underwent reversal of a loop ileostomy following low anterior resection for rectal cancer over period of five years, were involved in this study. All patients have CE and FS to check the patency of the anastomosis prior to reversal of ileostomy. The primary outcome was to investigate if routine CE adds clinically relevant information to a routinely performed FS by analysing concordance and diagnostic test accuracy. Secondary outcome to evaluate the accuracy of FS and CE in diagnosis of anastomotic stricture Results: 116 patients who had reversal of ileostomy had both CE and FS. Out of these, 110 (94.8%) had normal findings on CE and FS. Six patients had abnormal findings on either CE or FS. Two patients (1.7%) had anastomotic leak shown on CE study, despite normal findings on FS. One patient (0.8%) had a leak shown on both FS and CE. One patient (0.8%) had a leak shown on FS despite a normal CE study. Two patients (1.7%) had strictures shown on FS and stenosis on CE radiological reports. Conclusions: The discrepancies between Ce & FS are minimal. Although it has been suggested in previous studies that CE is of little value, the concurrent use of FS as well as CE is useful in identifying any trivial leak pre-reversal of ileostomy, and that will be valuable in decision making.